Vitamin D status and dietary calcium in chronic disease: Potential associations with metabolic syndrome and type 2 diabetes mellitus in Australian adults - Pannu, Poonam Kaur (Curtin University, 2017)
The thesis is based on data of a population sample of Victoria, Australia. Besides traditional factors, greater sitting time was a novel determinant of lower 25OHD. A systematic review and meta-analysis proposes a volumetric dilution and sequestration phenomenon accounts for the lower 25OHD in obesity. Greater 25OHD, calcium intake and their combination were significantly associated with a better biomedical risk profile, reduced adjusted odds for metabolic syndrome as well as type 2 diabetes.